2016
DOI: 10.3389/fpls.2016.00833
|View full text |Cite
|
Sign up to set email alerts
|

Combined Linkage and Association Mapping Reveals QTL and Candidate Genes for Plant and Ear Height in Maize

Abstract: Plant height (PH) and ear height (EH) are two very important agronomic traits related to the population density and lodging in maize. In order to better understand of the genetic basis of nature variation in PH and EH, two bi-parental populations and one genome-wide association study (GWAS) population were used to map quantitative trait loci (QTL) for both traits. Phenotypic data analysis revealed a wide normal distribution and high heritability for PH and EH in the three populations, which indicated that maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
91
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 66 publications
(73 reference statements)
9
91
0
2
Order By: Relevance
“…The percentages of phenotypic variation explained (R 2 ) by various markers analysed using AM were significant as those analysed using MapQTL 6.0. This is in agreement with previous studies reported in plants on efficiency and robustness of combining linkage mapping and AM for precise identification of QTL (Mammadov et al 2015; Li et al 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The percentages of phenotypic variation explained (R 2 ) by various markers analysed using AM were significant as those analysed using MapQTL 6.0. This is in agreement with previous studies reported in plants on efficiency and robustness of combining linkage mapping and AM for precise identification of QTL (Mammadov et al 2015; Li et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The integrated approach of linkage-AM has been used in other crop plants such as Arabidopsis (Sterken et al 2012), wheat (Shi et al 2017) and maize (Li et al 2016) to dissect quantitatively inherited traits. In tree species, an integrated method of linkage mapping and AM to decipher the nature of genetic architecture of potential QTLs for growth traits has been reported in poplar hybrids (Du et al 2016) and maritime pine (Bartholomé et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association study (GWAS), which is based on genetic linkage disequilibrium (LD) in a panel including a large number of genotypes representing broadly natural variations, has been used as an alternative approach for exploring the molecular basis and identifying SNPs of complex quantitative traits [2730]. In maize, GWAS has been successfully utilized to identify numerous candidate loci/genes controlling a serious of morphological or metabolic traits, such as drought tolerance [31], starch content [32], stalk cell wall components [33], plant height [34], herbivore-induced volatiles [35], male inflorescence size [36], shoot apical meristem size [37], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In A. thaliana , GWAS and QTL mapping are used to complement each other, overcoming their individual limitations (Tiwari et al ., ). In maize, the combination of QTL mapping and GWAS has been used to identify candidate genes for plant ear height and ear traits (Li et al ., ; Xiao et al ., ). The combination of the two methods has also been applied to detect loci governing agronomic traits in other species, like soya bean (Zhao et al ., ) and rice (Lou et al ., ).…”
Section: Discussionmentioning
confidence: 99%